Identifying Field-Independent Cognitive Styles of Junior High School Students on Numeracy - Zulfa, Faradina Nilam; Sujadi, Imam; Riyadi, Riyadi (FKIP Universitas Lampung, 2024)
Numeracy encompasses not only the manipulation of numbers and their operations, but also the application of concepts, procedures, facts, and mathematical tools to problem solving. In numeracy, there are cognitive levels that form a hierarchy of thinking, which includes knowing, applying, and reasoning. The cognitive level of reasoning involves the process of formulating problems, using mathematical concepts or procedures, and interpreting solutions in real-life contexts. To reach this level, analytical thinking is required, as FI individuals have a tendency to organize unorganized objects and vice versa. This research aims to describe how FI students use their numeracy skills to solve social arithmetic problems that arise in daily life at each cognitive numeracy level. A case study design was chosen as an alternative to achieve research objectives. Data collection was carried out using test-based interviews. Students are given two stimuli related to ratios and percentages, with each stimulus having three questions adjusted to the cognitive level of numeracy and followed by an interview. The data is then reduced and presented until valid conclusions are obtained based on data saturation. The results of the research show that FI students are able to identify known things related to ratios/percentages and explain the concept of ratios/percentages in solving social arithmetic problems. They are able to create mathematical models and apply these models to solve social arithmetic problems, provided that they pay more attention to writing down the solution steps to minimize writing errors. FI students can draw conclusions based on ratio/percentage information and provide arguments to support claims related to ratios/percentages in solving social arithmetic problems. If FI students remember to always use notation, the conclusions they draw will be correct. The research's three FI students met the indicators, but there are a few points that need further emphasis. Keywords: numeracy, cognitive level, field-independent, ratio and proportion.DOI: http://dx.doi.org/10.23960/jpmipa/v25i1.pp373-385